PENGARUH ONLINE SHOP JEJARING SOSIAL TERHADAP PERILAKU KONSUMTIF PADA IBU RUMAH TANGGA KABUPATEN MOJOKERTO (STUDI KASUS IBU RUMAH TANGGA DI DESA MOJOTAMPING, KECAMATAN BANGSAL, KABUPATEN MOJOKERTO) - Sari, Dian Eka; Handoko, Rudy; Rochim, Achludhin Ibnu (Universitas 17 Agustus 1945 Surabaya, 2018)
Globalization makes many changes and developments in information technology. Informationand communication technology which is currently widely used is the internet. Through the internetpeople can communicate and exchange information easily without the constraints of time and place.Nowadays that are in demand by the public is to shop online, there are many sites to shop online oneof which is social networking. Currently among housewives are actively participating in onlineshopping. If someone buys the goods based on selfish desires without the uses and benefits of aproduct will make people behave consumptive. This study uses a quantitative approach to thepopulation, namely housewives who never shop online. Samples are taken by 30 respondentsdetermined by purposive sampling technique. Data were collected by questionnaires. Analysis of datausing correlation analysis, determination analysis, parsial test. With IBM SPSS 22. The resultsshowed a significant influence between onlineshop social networks on consumer behavior with theregression equation at 0.528, correlation of 0.333 means that the relationship is low but definite,Determination of 0.111 means that effect by 11%, and t test of 1,870, which means onlineshop socialnetworks significantly influence consumer behavior.Keywords: Online Shopping, Social Networking, Consumer Behavior